Relation of personality factors and life events to waist/height ratio and percentage of visceral fat in women and men - Slepecky, Milos; Kotianova, Antonia; Prasko, Jan; Majercak, Ivan; Kotian, Michal; Gyorgyova, Erika; Zatkova, Marta; Chupacova, Michaela; Ociskova, Marie; Sollar, Tomas (Psychology research and behavior management, 2019)
PURPOSE: The investigation aimed to explore the association between personality traits, stressful life events, quality of life on anthropometric characteristics (waist/height ratio and percentage of visceral fat). METHOD: A total of 227 participants took part in this cross-sectional study. Participants completed the Social Readjustment Rating Scale (SRRS), Temperament and Character Inventory-Revised, Type-D Scale (DS-14), EuroQol Group 5-Dimension Self-Report Questionnaire (EQ-5D), and demographic questionnaire. Two anthropometric parameters were measured: Waist/height ratio and Percentage of the visceral fat. RESULTS: The average age of participants was 39.6±12.9 years, 60.4% women. The 41.8% of participants were overweight or obese. Regression analysis found a significant link between Harm-avoidance and EQ-5D visual analog scale (VAS) with Waist/height ratio in women and Reward dependence and Cooperativeness with Waist/height ratio in men. In regression analysis, the score of life events (SRRS) has statistically significant linked to Percentage of the visceral fat in women. The regression analysis also found a significant link between Novelty seeking, DS14, Negative affectivity, and EQ-5D VAS with Percentage of the visceral fat in women. CONCLUSION: Significant associations between live events, personality traits, and body anthropometric measures were recognized. The differences were recognized between women and men. Outcomes propose some promising tools by which personality factors may influence overweight and obesity.
Keywords: anthropometric characteristics; life events; quality of life; overweight; negative affectivity; personality traits; sex differences